Pengaruh Dimasukkannya Band Inframerah Thermal Data Landsat Thematic Mapper Pada Saat Klasifikasi Terhadap Ketelitian Keseluruhan Dan Kesalahan Individu - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
Objective of the study was to study the effect of inclusion thermal infrared of Landsat TM data during classification on the overall accuracy and individual error. Method applied was by classifying (by using Maximum Likelihood classifier) images consisting of different band combinations. A first combination was chosen by excluding Thermal Infrared Band (and is used as Master during comparison). Other classification processes were applied similarly with the inclusion of Thermal Infrared Band (the results were used as Slave fir comparison purpose). ). Comparison was conducted by using Overlay Analysis between Master and Slave. The result was an Error Matrix depicting the existence of Overall and Individual Error. Individual Error consists Commission and Omission of Errors. The result shows that the inclusion of Thermal Infrared Band in the landuse classification gave the overall accuracy reduction about 39.19 %, commission of error 54.86 %, and omission of error 40.81 % compared to those classification resulted when Thermal Infrared Band was excluded